2020
DOI: 10.1177/1932296820951829
|View full text |Cite
|
Sign up to set email alerts
|

Current Strategies for the Management of Painful Diabetic Neuropathy

Abstract: The development of painful diabetic neuropathy (PDN) is a common complication of chronic diabetes that can be associated with significant disability and healthcare costs. Prompt symptom identification and aggressive glycemic control is essential in controlling the development of neuropathic complications; however, adequate pain relief remains challenging and there are considerable unmet needs in this patient population. Although guidelines have been established regarding the pharmacological management of PDN, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0
5

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(45 citation statements)
references
References 135 publications
0
34
0
5
Order By: Relevance
“…The first treatment for pain, including chronic pain, is often pharmacotherapy, but neuropathic pain is not the same as musculoskeletal pain, and commonly used analgesics such as opioids are not appropriate or effective for managing chronic neuropathic pain such as PDN [15,16]. The pharmacotherapies approved and used to manage PDN are mostly not traditional analgesics or opioids that can be taken "as needed" but rather agents such as anticonvulsants or antidepressants that must be taken regularly for a period of time to achieve full effect [17]. There are now more pharmacotherapies available for treating PDN than in the recent past, which are summarized in Table 2, and clinicians should consider patient-specific factors such as age, quality-of-life goals, functional status, and comorbidities when determining appropriate management [3,[18][19][20].…”
Section: Pharmacotherapymentioning
confidence: 99%
See 3 more Smart Citations
“…The first treatment for pain, including chronic pain, is often pharmacotherapy, but neuropathic pain is not the same as musculoskeletal pain, and commonly used analgesics such as opioids are not appropriate or effective for managing chronic neuropathic pain such as PDN [15,16]. The pharmacotherapies approved and used to manage PDN are mostly not traditional analgesics or opioids that can be taken "as needed" but rather agents such as anticonvulsants or antidepressants that must be taken regularly for a period of time to achieve full effect [17]. There are now more pharmacotherapies available for treating PDN than in the recent past, which are summarized in Table 2, and clinicians should consider patient-specific factors such as age, quality-of-life goals, functional status, and comorbidities when determining appropriate management [3,[18][19][20].…”
Section: Pharmacotherapymentioning
confidence: 99%
“…In addition to duloxetine, the SNRI venlafaxine and TCAs have shown evidence of efficacy for PDN and may be considered for PDN according to recommendations by the ADA, although they have not received FDA approval for this use [18]. Venlafaxine is mechanistically similar to duloxetine, but there are fewer published data for this drug in PDN [17]. An extended release (ER) formulation of venlafaxine was tested in a 6-week, double-blind, RCT in 244 subjects with PDN, and the investigators found that doses from 150 mg to 225 mg/day resulted in 50% lower pain scores than the baseline, which was significantly greater than the 27% pain reduction in the placebo group [41].…”
Section: Antidepressantsmentioning
confidence: 99%
See 2 more Smart Citations
“…Yoga and neuropathy: Peripheral neuropathy is a common neurological condition due to physical nerve injury, diabetes mellitus, autoimmune disorders, malignancy, kidney failure, nutritional deficiencies, systemic disorders, and idiopathic neuropathies, which can implicate the motor, sensory, and/or autonomous peripheral nerves[ 102 , 103 ]. Several lines of evidence suggest that yoga may alleviate symptoms of various neuropathies[ 104 , 105 ].…”
Section: The Clinical Effect Of Yogamentioning
confidence: 99%